Optical coherence tomography imaging of excised canine apocrine gland anal sac adenocarcinoma tumours. (8th July 2020) - Dornbusch, Josephine A.; Selmic, Laura E.; Huang, Pin‐Chieh; Samuelson, Jonathan P.; Cocca, Christina; Wavreille, Vincent A.; Boppart, Stephen A.
Abstract: Optical coherence tomography (OCT) is an optical imaging modality that has been investigated for real‐time surgical margin evaluation in human breast cancer patients. Previous veterinary OCT studies have been limited to surgical margin imaging for soft tissue sarcoma (STS) tumours. To the authors knowledge, OCT has never been used to characterize or evaluate other types of neoplasia in dogs. The goal of this study was to characterize the OCT imaging appearance of apocrine gland anal sac adenocarcinoma (AGASACA) in excised ex vivo specimens from five client‐owned dogs. All excised tissue surgical margins were imaged using a clinical spectral domain OCT system and two to four areas suspicious for incomplete surgical margins were selected. These areas were inked and sections were trimmed for histopathology. This enabled OCT imaging from each area of interest to be compared with corresponding H&E stained histology imaging from the same location. OCT was able to identify the presence of AGASACA at or within 1 mm of the surgical margin in all areas of interest. AGASACA, similar to the previously described canine STS, generated a dense, highly scattering image without any specific textural architecture. This study was able to validate the ability of OCT to accurately identify another type of tumour presence at or close to the surgical margin in the dog. Further study is needed to assess OCT accuracy at identifying other tumour types in dogs to understand its potential clinical applications.